The tooth book - LeSieg, Theo., 1904-; McKie, Roy (New York : Beginner Books, 1981)
Rhyming text and illustrations briefly point out what animals have teeth, their uses, and how to care for them.
Elem. School Library Collection.
Bulletin (Center for Children's books).
2.6
K-3
Keywords: Teeth -- Fiction; Stories in rhyme; Teeth -- Fiction; Stories in rhyme; Teeth -- Fiction; Stories in rhyme